Research advances and trends in the surgical treatment of carpal tunnel syndrome from 2003 to 2022: A CiteSpace-based bibliometric analysis - Zheng, Daqiang; Wu, Zhiming; Li, Lu; Chen, Sichao; Chang, Jianjun (Frontiers in Neurology, 2023)
Background: Carpal Tunnel Syndrome (CTS) is one of the most common peripheral neuropathies. The typical symptoms are tingling and numbness in the median nerve distribution of the hand. Current treatment for CTS includes general conservative treatment and surgical treatment. Surgical treatment plays a crucial role in the management of CTS, but little bibliometric analysis has been conducted on it. Therefore, this study aimed to examine the progress and trends in the surgical treatment of CTS over the past 20 years using Citespace (6.1 R4). METHODS: Publications on the surgical treatment of CTS in the Web of Science database were collected between 2003 and 2022. CiteSpace software was applied to visualise and analyse publications, countries, institutions, journals, authors, references and keywords. RESULTS: 336 articles were collected, with the USA being the major publishing power in all countries/regions. JOURNAL OF HAND SURGERY AMERICAN VOLUME was the journal with the most published and co-cited articles. Based on keyword and reference co-citation analysis, keywords such as carpal tunnel syndrome, surgery, release, median nerve, and diagnosis were the focus of the study. CONCLUSION: The results of this bibliometric study provide clinical research advances and trends in the surgical treatment of patients with CTS over the past 20 years, which may help researchers to identify hot topics and explore new directions for future research in the field.